Fracionamento de fósforo inorgânico em solos do semiárido adubados com fósforo - Tavares, Hernane Arllen Medeiros (Universidade Federal Rural do Semi-Árido, 2019)
Phosphorus (P) is a of the most researched nutrients in soil chemistry and fertility studies. This is due to the fact that the dynamics of this chemical element in the soil-plant system is very complex, given the strong interaction of this nutrient with the soil. For a better understanding of the dynamics of P, it is necessary to know the different fractions of this element in the soil. The objective of this work was to evaluate the inorganic P fractions in semi-arid soils after receiving phosphate fertilization, and to correlate them with chemical and physical characteristics of these soils. Samples of nine soils representative of the semi-arid region between the Piranhas-Açu (RN) and Jaguaribe (CE) rivers were collected in the 0-30 cm layer and then characterized chemically and physically. Then, these soil samples were fertilized with P and then incubated during the period of 30 days. After the incubation period, the soil samples were analyzed chemically for the quantification of inorganic P (P-H2O, P-Al, P-Fe and P-Ca) fractions in these soils. In the studied soils, there was a high correlation between the maximum phosphorus sorption capacity (CMSP) and the values of remaining phosphorus (P-rem) (r = -0.95) and clay (r = 0.94). The clay contents also correlated well with the P-rem values (r = -0.94), showing that in these soils the clay content is as efficient as the P-rem to estimate the phosphorus capacity factor (PCF) of the soils. Phosphate fertilization did not increase P-H2O contents in the studied soils, but increased the contents of all other fractions of inorganic Pi. In the presence of phosphate fertilization, the levels of P-Al found in Ca2+ rich soils maybe in fact a part of the P-Ca fraction that may have been extracted by the extractor used to extract P-Al.
Monografia
Keywords: Disponibilidade de fósforo; Solos calcários; Sorção de fósforo; Availability of phosphorus; Calcareous soils; Sorption of phosphorus; CIENCIAS AGRARIAS::AGRONOMIA